Pengaruh Corporate Governance, Leverage, Dan Profitabilitas Terhadap Manajemen Laba - Dina Listiyani; Cahyani Nuswandari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Financial statements are one of the benchmarks for measuring company performance, and until now the phenomenon of earnings management is still often found. This study aims to examine empirical evidence regarding the effect of corporate governance, the proportion of the board of commissioners, leverage, and profitability on earnings management. Earnings management is an act of manipulating earnings information carried out by management with the aim of benefiting itself. The population of this study were 254 companies in the primary consumer goods sector listed on the Indonesia Stock Exchange in 2019 - 2021. With the purposive sampling data collection method, the research sample was obtained as many as 171 companies. When testing there is residual data that is not normally distributed, outliers are carried out, so that the data processed further is 101 companies. This study provides evidence that managerial ownership and audit committee have a significant negative effect, and institutional ownership has a significant positive effect on earnings management, while the proportion of independent commissioners, leverage, and profitability have no significant effect on earnings management.